Highway infrastructure health monitoring using micro-electromechanical sensors and systems (MEMS) - Ceylan, Halil; Gopalakrishnan, Kasthurirangan; Kim, Sunghwan; Taylor, Peter C.; Prokudin, Maxim; Buss, Ashley F. (Journal of Civil Engineering and Management, 2014)
The development of novel “smart” structures by embedding sensing capabilities directly into the construction material during the manufacturing and deployment process has attracted significant attention in autonomous structural health monitoring (SHM). Micro-electromechanical systems (MEMS) provide vast improvements over existing sensing methods in the context of SHM of highway infrastructure systems, including improved system reliability, improved longevity and enhanced system performance, improved safety against natural hazards and vibrations, and a reduction in life cycle cost in both operating and maintaining the infrastructure. Advancements in MEMS technology and wireless sensor networks provide opportunities for long-term, continuous, real-time structural health monitoring of pavements and bridges at low cost within the context of sustainable infrastructure systems. Based on a comprehensive review of literature and vendor survey, the latest information available on off-the-shelf MEMS devices, as well as research prototypes, for bridge, pavement, and traffic applications are synthesized in this paper. In addition, the paper discusses the results of a laboratory study as well as a small-scale field study on the use of a wireless concrete monitoring system based on radio-frequency identification (RFID) technology and off-the-shelf MEMS-based temperature and humidity sensors.